Endoscopic Submucosal Dissection for Early Gastric Neoplasia Occurring in the Remnant Stomach after Distal Gastrectomy - Ji Young Lee; Byung-Hoon Min; Jung Gyu Lee; Donghyo Noh; Jun Haeng Lee; Poong-Lyul Rhee; Jae J. Kim (Korean Society of Gastrointestinal Endoscopy, 2016)
Background/Aims: Endoscopic submucosal dissection (ESD) for tumors occurring in the remnant stomach is technically difficult to perform because of limited working space and severe fibrosis and staples present around the suture line. We aimed to elucidate the feasibility and clinical outcomes of performing ESD for tumors in the remnant stomach. Methods: Between December 2007 and January 2013, 18 patients underwent ESD for tumors (six adenomas and 12 differentiated-type early gastric cancers [EGCs]) occurring in the remnant stomach after distal gastrectomy. Clinicopathologic features and clinical outcomes after ESD were retrospectively analyzed. Results: Two-thirds of the lesions were located on the body, and half were located on the suture line. En bloc resection, R0 resection, and en bloc with R0 resection rates were 88.9%, 100%, and 88.9%, respectively. Curative resection rate for EGC was 91.7%. Perforation occurred in one patient (5.6%) and was successfully managed by endoscopic closure with metallic clips and conservative management. There was no significant bleeding after ESD. During a median follow-up of 47.5 months, no local, metachronous, or extragastric recurrence was seen for either EGC or adenoma lesions. Conclusions: ESD is a feasible and effective treatment modality and can be considered a primary intervention for early gastric neoplasia occurring in the remnant stomach.